Molecular Mechanism of β-Sitosterol and its Derivatives in Tumor Progression - Bao, Xingxun; Zhang, Yanan; Zhang, Hairong; Xia, Lei (Frontiers in Oncology, 2022)
β-Sitosterol (SIT), a white powdery organic substance with a molecular formula of C29H50O, is one of the most abundant naturally occurring phytosterols in plants. With a chemical composition similar to that of cholesterol, SIT is applied in various fields such as medicine, agriculture, and chemical industries, owing to its unique biological and physicochemical properties. Modern pharmacological studies have elucidated good anti-tumor therapeutic effect activity of SIT, which mainly manifests as pro-apoptotic, anti-proliferative, anti-metastatic, anti-invasive, and chemosensitizing on tumor cells. In addition, SIT exerts an anti-tumor effect on multiple malignant tumors such as breast, gastric, lung, kidney, pancreatic, prostate, and other cancers. Further, SIT derivatives with structural modifications are promising anti-tumor drugs with significant anti-tumor effects. This review article focuses on recent studies relevant to the anti-tumor effects of SIT and summarizes its anti-tumor mechanism to provide a reference for the clinical treatment of malignant tumors and the development of novel anti-tumor drugs.